Metodología para la determinación de características del viento y evaluación del potencial de energía eólica en Túquerres-Nariño - Eraso Checa, Francisco; Escobar Rosero, Edisson (Revista Científica, 2018)
The world is living a steady increase in the electric power demand, an alternative power generation different to conventional is the renewable energy. With the appearance of the Law 1715, Colombia has an incentives policy for the integration of new projects in renewable energies. Because of that, is important to develop studies with real data in the field of the potential of renewable energy resources which can be implemented. This article presents the analysis of the wind generation potential of Túquerres Savanna, located in the department of Nariño. The potential was obtained from the measurement of the wind speed, during the period between the months of June and December of the year 2015. The data were analyzed statistically according to a measure of central tendency, frequency distribution and Weibull distribution for the normalization of scattered data; finally, the power density was calculated according to a horizontal axis wind turbine and the electrical generation potential of the area was simulated. The average wind speeds are 4,4 m/s and the power density founded is 3,47 W/m2.